Concise Review: Modeling Multiple Sclerosis With Stem Cell Biological Platforms: Toward Functional Validation of Cellular and Molecular Phenotypes in Inflammation‐Induced Neurodegeneration. (15th January 2015) - Orack, Joshua C.; Deleidi, Michela; Pitt, David; Mahajan, Kedar; Nicholas, Jacqueline A.; Boster, Aaron L.; Racke, Michael K.; Comabella, Manuel; Watanabe, Fumihiro; Imitola, Jaime
Abstract : This review discusses the application and challenges of somatic cell reprogramming and induced pluripotent stem cell technology technologies, including the generation of neurons, oligodendrocytes, and oligodendrocyte progenitor cells (OPCs) from patients and novel stem cell and OPC cellular arrays, in the discovery of new mechanistic insights and the future development of MS reparative therapies. Abstract : In recent years, tremendous progress has been made in identifying novel mechanisms and new medications that regulate immune cell function in multiple sclerosis (MS). However, a significant unmet need is the identification of the mechanisms underlying neurodegeneration, because patients continue to manifest brain atrophy and disability despite current therapies. Neural and mesenchymal stem cells have received considerable attention as therapeutic candidates to ameliorate the disease in preclinical and phase I clinical trials. More recently, progress in somatic cell reprogramming and induced pluripotent stem cell technology has allowed the generation of human "diseased" neurons in a patient‐specific setting and has provided a unique biological tool that can be used to understand the cellular and molecular mechanisms of neurodegeneration. In the present review, we discuss the application and challenges of these technologies, including the generation of neurons, oligodendrocytes, and oligodendrocyte progenitor cells (OPCs) from patients and novel stem cell and OPC cellular arrays, in the discovery of new mechanistic insights and the future development of MS reparative therapies.